Investigating the effect of gas flow rate on the drag reduction performance in gas oil-solid gas flow system - Nor' Aqilah, Norahzan (2012)
Phenomenon on drag reduction in gas-liquid system has to be emphasized in the past decade because of the importance in academic and industry.Drag has long been identified as the main reason for the loss of energy in fluid transmission like pipelines and other similar transportation channels. The main contributor to this drag is the turbulence of the flow as well as friction against the pipe walls,which will results in more pumping power consumption,increasing in production rates, pipelines capabilities and faster transportation.In this study,injection of gas into the pipe flow as a drag reducing agent was investigated.The experimental procedure also investigates the effects of liquid flow rate,powder addition concentration and particle size of suspended solid.The gas that used to inject in the pipelines is an air gas.Particular attention was focused to the influence on the pressure drop due to the injection of air gas into the horizontal 1.5 inch or 0.0381 meter pipe flow.The experimental results showed that the drag reduction is more superior towards bigger particle sizes,higher in liquid flow rate of diesel concentration and increasing the solid addition concentration. Percentage of drags reduction increases by increasing the particle size.The maximum percentage of drag reduction in the 630µm particle size with 300ppm solid addition concentration for 9.5m³/h liquid flow rate is 61.43%.